The Stability and Bifurcation of the (2m+1)th-Degree Polynomial Systems - Luo, Albert C J (Journal of Vibration Testing and System Dynamics, 2026)
In this paper, the global stability and bifurcations of equilibriums in the (2m+1)th -degree polynomial system are discussed for a better understanding of the complexity of bifurcations and stability of equilibriums in such a (2m+1)th-degree polynomial system. The appearing and switching bifurcations for simple and higher-order equilibriums are presented. The broom-teethcomb-appearing, broom-spraying-appearing, and broom-sprinkler-spraying-appearing bifurcations for simple and higher-order equilibriums are presented. The antenna-switching bifurcations for simple and higher-order equilibriums are discussed, and the parallel straw-bundle-switching and ower-bundle-switching bifurcations for simple and higher-order equilibriums are also presented.